CODE-SWITCHING IN THE ENGLISH TEACHING TO NON-ENGLISH DEPARTMENT STUDENTS - Yusuf Al Arief; Siti Haniifah Husnul Khotimah (STKIP PGRI Lubuklinggau, 2019)
Code-switching is a phenomenon studied in sociolinguistics. It exists in multilingual societies like in Indonesia, where people use more than one language to communicate including in classroom interaction, especially in the process of teaching English as a foreign language. This research aimed to find out the types and the functions of code-switching used by English lecturers in teaching English to Non-English Department Students at FKIP of Lambung Mangkurat University in the Academic Year of 2017/2018. This research was conducted through the descriptive-qualitative method. The subjects were the lecturers of English class for Non-English Department Students or Mata Kuliah Dasar Umum (MKDU) Bahasa Inggris Class. The researchers used observations and confirmed the results from the interviews. The data were analyzed by data reduction, data display, and conclusion drawing or verification. The research result indicated that in the process of teaching English, the lecturers sometimes switched their languages: English, Bahasa Indonesia, Banjarese, and Arabic. There were three types of code-switching used by the lecturers which were tag-switching, intrasentential-switching, and intersentential switching. While for the function, there were three functions of code-switching used by the lecturers which were topic-switch, affective-function, and repetitive function. In conclusion, the lecturers switched their languages in some types and for various functions depending on the situation of their teaching activity and students’ need